An analysis of large Forbush decrease events using phase diagrams of view channels of the Nagoya multidirectional muon telescope. (February 2015) - Kalugin, G.; Kabin, K.
Abstract: Large Forbush decrease (FD) events are analysed using data recorded by the ground-based Nagoya multi-directional muon telescope in Japan. As a part of the analysis we introduce a phase diagram for the channels of telescope, which provides more robust information about characteristics of events. Specifically, the slope of the regression line in the phase diagram represents the FD amplitude which can be computed for different channels. This allows us to analyze the dependence of the FD amplitude on the rigidity of CR particles. Two models for this dependence are considered, a power law and exponential and the former is found to be more suitable for the considered events. In terms of the power-law index and the FD amplitude the events are split into two groups. It is shown that the larger events are characterized by smaller power-law index than the smaller ones. Highlights: We analyse large Forbush decrease events using data from Nagoya muon telescope. We introduce a phase diagram for the channels of telescope. A power-law dependence of Forbush decrease amplitude on particle rigidity is found. The events are split into two groups in terms of the power-law index.